1970
DOI: 10.1029/ja075i031p06233
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial aurora/airglow in the far ultraviolet

Abstract: Far ultraviolet emissions in the equatorial zone have been detected at altitudes of less than 500 km with an experiment aboard the Ogo 4 polar‐orbiting satellite. The occurrence frequency reached a maximum in both late October and early March during the period August 1967 to May 1968. Both maximums occurred near 2130 local time. Low values during June 1968 indicate a strong seasonal dependence. The emissions were seen quite symmetrically in position at 12°–15° on either side of the magnetic dip equator complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…The OI 135.6 nm emission from the low latitude ionosphere was first observed by the OGO-4 satellite, and it was observed that the low-latitude ionosphere had two emission peaks located 10°-20°from the geomagnetic equator corresponding to peaks of the plasma density of the equatorial anomaly (EA) or a.k.a. Appleton anomaly (Hicks and Chubb 1970;Barth and Schaffner 1970). Huba et al (2002) reported that the O + density deduced from the OI 135.6 nm limb scan data agrees well with the SAMI2 ionosphere model.…”
Section: Nighttime Ionospheresupporting
confidence: 68%
“…The OI 135.6 nm emission from the low latitude ionosphere was first observed by the OGO-4 satellite, and it was observed that the low-latitude ionosphere had two emission peaks located 10°-20°from the geomagnetic equator corresponding to peaks of the plasma density of the equatorial anomaly (EA) or a.k.a. Appleton anomaly (Hicks and Chubb 1970;Barth and Schaffner 1970). Huba et al (2002) reported that the O + density deduced from the OI 135.6 nm limb scan data agrees well with the SAMI2 ionosphere model.…”
Section: Nighttime Ionospheresupporting
confidence: 68%
“…Measurements of night sky emissions have been made at visible wavelengths from the ground [Tinsley et al, 1973;Tinsley and Bittencourt, 1975] and at ultraviolet wavelengths from space [Hicks and Chubb, 1970;Barth and Shaffner, 1970]. These observations led to the identification of two possible production mechanisms for the emission: radiative recombination of O + ions and electrons [Hanson, 1969] [Knudsen, 1970].…”
Section: Introductionmentioning
confidence: 99%
“…The emis sions are pro duced by ra di a tive re com bi na tion of O + ions and elec trons to pro duce atomic ox y gen in an ex cited state that sub se quently de cays by emit ting a pho ton. These emis sions have been ob served at vis i ble wave lengths (7774 and 8446 Å) from the ground (Tinsley et al 1973;Tinsley and Bittencourt 1975) and at ultraviolet wave lengths (911, 1304, and 1356 Å) from space (Barth and Shaffner 1970;Hicks and Chubb 1970;Cha krabarti et al 1984;Feldman et al 1992). The use of night time O emis sions to re motely sense the F-re gion elec tron den sity is de scribed by Chandra et al (1975), Tinsley and Bittencourt (1975), Meier (1991), and Dymond et al (1996Dymond et al ( , 1997.…”
Section: Introductionmentioning
confidence: 99%